Government procurement and financial statement certification: Evidence from private firms in emerging economies - Hope, Ole-Kristian; Jiang, Shushu; Vyas, Dushyantkumar (Journal of International Business Studies, 2021)
In this paper, we examine the monitoring role of government customers in emerging markets, a setting where public procurement is significant but the procurement institutions are weak. In these countries, financial statement certifications could be an important mechanism for a private firm to facilitate contracting with governments. Employing a sample of private firms across 98 emerging economies, we first document in-depth private-firm audit regulations for each country. We find that firms are more likely to have financial statements certified by an external auditor when they have government contracts. We further find that the association is less pronounced when governments have weaker monitoring incentives – when suppliers are subject to monitoring from tax authorities or creditors, when government contracting officials receive bribes, and when government spending is less transparent. We corroborate our inferences using the staggered adoption of an E-Procurement system to infer changes in governments’ monitoring incentives and several other robustness checks.